Epidemiological profile of patients with malignant breast neoplasia in the northern region of Minas Gerais - Paranhos Magalhães, Nathália; Veloso Pereira, Gustavo; Lúcia Carvalho Prates, Cléia; Cezar Lancuna, Alex; Godinho Gonçalves, Romeu; Vinícius Macedo Oliveira, Marcos; Ramos Espírito-Santo, Luçandra; Andrade de Prince, Karina (Revista Unimontes Científica, 2020)
PERFIL EPIDEMIOLÓGICO DE PACIENTES COM NEOPLASIA MALIGNA DE MAMA NA REGIÃO NORTE DE MINAS GERAIS Epidemiological profile of patients with malignant breast neoplasia in the northern region of Minas Gerais Abstract: Breast cancer is a public health problem in Brazil and the world and is the most frequent malignant neoplasm in the female gender. Objective: The objective of this study was to know the epidemiological profile of breast cancer in the North of Minas Gerais, Brazil, from 2008 to 2017. Methodology: This was a cross - sectional, retrospective, quantitative, descriptive study using DATASUS secondary data regarding breast cancer hospitalizations in the northern region of Minas Gerais, from January 2008 to December 2017. Descriptive analyzes were performed using absolute values (n), relative (%), and mean using Excel® 12.0 software. Results: Of the hospitalizations for breast cancer in the period and region analyzed, 97.74% were female, 26.51% were in the age group 50-59 years old, 71.65% were brown, representing an average of 239.5 (± 78.1) hospitalizations per year and 17.6 (± 6.2) deaths per year, of which 26.14% occurred in the age range from 50-59 years. Conclusion: The prevalence of hospitalizations for breast cancer was higher among women, brown breed, in the age group from 50 to 59 years. These numbers increased in the period from 2009 to 2015, the absolute number of deaths remained practically constant over the years, and the mortality rate increased progressively with age and was considerably higher in males. Resumo: O câncer de mama é um problema de saúde pública no Brasil e no mundo, sendo a neoplasia maligna mais frequente no sexo feminino. Objetivo: Conhecer o perfil epidemiológico do câncer de mama no Norte de Minas Gerais, no período de 2008 a 2017. Metodologia: Trata-se de um estudo transversal, retrospectivo, quantitativo, de caráter descritivo, no qual se utilizaram dados secundários do Departamento de Informática do Sistema Único de Saúde (DATASUS), referentes às internações por câncer de mama na macrorregião de saúde do norte de Minas Gerais, no período de janeiro de 2008 a dezembro de 2017. Foram processadas análises descritivas por meio de valores absolutos (n), relativos (%) e média, através do software Excel® 12.0. Resultados: Das internações por câncer de mama no período e região analisados, 97,74% eram do sexo feminino, 26,51% na faixa etária de 50 a 59 anos, 71,65% pardas, que representaram uma média de 239,5 (±78,1) internações por ano e de 17,6 (±6,2) óbitos por ano, dos quais 26,14% ocorreram na faixa etária de 50 a 59 anos. Conclusão: A prevalência de internações por câncer de mama foi maior entre mulheres, pardas, na faixa etária de 50 a 59 anos. Esses números cresceram no período de 2009 a 2015, o número absoluto de óbitos manteve-se praticamente constante ao longo dos anos, a taxa de mortalidade aumentou progressivamente com a idade e foi consideravelmente mais alta no sexo masculino.